Obstacles to prediction of outcome in pediatric cardiomyopathy. (June 2018) - Colan, Steven D.
Abstract: The 4th International Conference on Cardiomyopathy in Children (4th ICCC), held May 18-19th, 2017, in Bethesda, Maryland, included a session titled "Current Controversies in Diagnosis and Management" which focused on three presentations concerning management issues that represent persistent sources of disagreement within the field: "Management and Indications for Transplant in Restrictive Cardiomyopathy" presented by Dr. Elizabeth Blume, "Evidence Concerning Efficacy of Exercise Restriction in Hypertrophic Cardiomyopathy" presented by Dr. Mark Friedberg, and "Indications for Primary Prevention ICD Implantation in Children with Hypertrophic Cardiomyopathy" presented by Dr. Dominic Abrams. These presentations centered on decision making intending to avert poorly predictable outcomes in rare disorders and, as such, are exemplary of the obstacles encountered when providing care to patients with rare diseases. The principle observation is that rare outcomes, in general, require predictors with very high sensitivity and specificity in order to provide a significant improvement in care, and each of the clinical situations described here is lacking in this regard. Highlights: Presentations from the 4th International Conference on Cardiomyopathy in Children. Controversial topics in management of pediatric cardiomyopathy are discussed. Guidelines for management of pediatric cardiomyopathy are highly controversial. In rare diseases more sensitive and specific outcome predictors are needed.